Vehicle identifiers: The key to jumpstarting the European Green Auto ABS market? - Angelina Hackmann; Vincent Lindner; Loriana Pelizzon; Max Riedel (Leibniz Institute for Financial Research SAFE, 2024)
This paper addresses the need for transparent sustainability disclosure in the European Auto AssetBacked Securities (ABS) market, a crucial element in achieving the EU's climate goals. It proposes the use of existing vehicle identifiers, the Type Approval Number (TAN) and the Type-Variant-Version Code (TVV), to integrate loan-level data with sustainability-related vehicle information from ancillary sources. While acknowledging certain challenges, the combined use of TAN and TVV is the optimal solution to allow all stakeholders to comprehensively assess the environmental characteristics of securitised exposure pools in terms of data protection, matching accuracy, and cost-effectiveness.
Keywords: 330; Securitisation; Car Loans; Sustainable Finance; Regulation